1984
DOI: 10.1104/pp.75.4.1044
|View full text |Cite
|
Sign up to set email alerts
|

Salinity Effects on Photosynthesis and Growth in Alternanthera philoxeroides (Mart.) Griseb.

Abstract: Alternantheraphiloxeroides, alliator weed, was grown at five different NaCI concentrations to determine the effect of salinity on factors related to the net rate of CO2 uptake (Pa). Over the range of 0 to 400 millimolar NaCI, P. declined 51%. Stomatal conductance declined in parallel with P. and as a result there was no reduction in intercellular CO2 concentration and therefore no reduction in the amount of CO2 available for photosynthesis. The CO2 compensation point did not change with salt stress. Increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

1985
1985
2002
2002

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 23 publications
1
20
1
Order By: Relevance
“…Direct effects of excess salt on various plant biochernical and structural functions which can cause reductions in P, capacity have been documented by Chimikhs & Karlander (1973), Helal & Mengel (1981, and Longstreth et al (1984).…”
Section: Discussionmentioning
confidence: 90%
“…Direct effects of excess salt on various plant biochernical and structural functions which can cause reductions in P, capacity have been documented by Chimikhs & Karlander (1973), Helal & Mengel (1981, and Longstreth et al (1984).…”
Section: Discussionmentioning
confidence: 90%
“…Similar responses to salinity have been previously documented for S. patens (Pezeshki et al 1987). Stomata1 closure in response to salinity has been reported for several species (Downton 1977, Kemp & Cunningham 1981, Longstreth et al 1984, Pearcy & Ustin 1984. The decrease in A found in response to salinity may be attributed both to stomata1 control (Downton 1977, Longstreth & Strain 1977 and to non-stomata1 (metabolic) factors ( 1979, Walker et al 1982, Longstreth et al 1984.…”
Section: Discussionmentioning
confidence: 99%
“…Pearcy & Ustin (1984) found reductions in A rates in Spartina and Scirpus species as a result of diffusional limitations and metabolic effects when soil salinity increased. Longstreth et al (1984) reported 51 O/O reduction in A for Alternanthera philoxerides plants after salt application. In the present study, recovery trends were noted for A after initial reductions, indicating some photosynthetic acclimation/adaptation to salinity conditions in both populations, but recovery appeared to be more pronounced in Ferblanc population (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators concluded that chloroplasts rather than CO2 diffusion processes are the primary control of photosynthesis under different kinds of environmental stress (2,6,14). However, several recent reports have suggested that photosynthesis of plants exposed to salinity, as measured under saturating CO2 concentrations, was not greatly altered (4,5,22).…”
Section: Methodsmentioning
confidence: 99%